2021
DOI: 10.1177/21501327211054996
|View full text |Cite
|
Sign up to set email alerts
|

Age-Adjusted D-Dimer in the Prediction of Pulmonary Embolism: Systematic Review and Meta-analysis

Abstract: Background: Pulmonary embolism (PE), depending on the severity, carries a high mortality and morbidity. Proper evaluation, especially in patients with low probability for PE, is important to avoid unnecessary diagnostic testing. Objective: To review the diagnostic utility of conventional versus age-adjusted D-dimer cutoff values in patients 50 years and older with suspected pulmonary embolism. Methods: Systematic review with univariant and bivariant meta-analysis. Data sources: We searched PubMed, MEDLINE, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…In addition, previous studies have shown that the plasma D-dimer level of patients with lung cancer is generally high, which is greatly affected by age, and the difference in lung cancer stage and pathological type may change the optimal critical value for the diagnosis of PE with plasma D-dimer. 44,45 Subgroup analysis based on lung cancer stage and pathological type needs to be further explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have shown that the plasma D-dimer level of patients with lung cancer is generally high, which is greatly affected by age, and the difference in lung cancer stage and pathological type may change the optimal critical value for the diagnosis of PE with plasma D-dimer. 44,45 Subgroup analysis based on lung cancer stage and pathological type needs to be further explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…So, in elderly patients, the D-dimer level should be adjusted by age. Currently, many studies have already reported the age-adjusted D-dimer cutoff values in elderly patients ( 43 45 ). However, there has been no such a concrete and unified calculation formula about the age-adjusted D-dimer.…”
Section: Discussionmentioning
confidence: 99%
“…But, compared to age adjusted D-dimer, conventional D-dimer use is associated with higher false positive results. 6 The formula to calculate age-adjusted D-dimer is Age (if over 50 years) x 10 = cutoff value in ng/mL (fibrinogen equivalent units).…”
Section: Triage For Imaging/diagnosismentioning
confidence: 99%